(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In generally nutrition defined the process of taking in different food stuffs and using it for physical growth of a human body. A nutrient element is a fundamental requirement for proper growth of a human body which provides not only physical power but also the proper psychological thinking, active mentality, moral power as well as balance health in human body. Tehsil Pathalgaon is taken to be as unit of study which is basically tribal populated areas and economically depends on agricultural activities, Mahua liquor business and predominantly agro-based industry. It is situated in south-western corner of Jashpur district. According to census 2011- the total population is 168112 persons, total households is 38244, the total gram Panchayats is 83, total number of villages is 107 in Tehsil Pathalgaon and the total Geographical area of Tehsil Pathalgaon is 941.41 Sq. kms. The total number of scheduled tribe’s population is 112332 persons. The main objectives of the present study are to analyze the emerging nutritional levels of Oraon tribes in Tehsil Pathalgaon of Jashpur district. This research paper has been based on both the primary data and secondary data. ICMR’s recommends norms are used for assess the emerging nutritional levels of Oraon tribes in Tehsil Pathalgaon. The processed data is analyzed with the help of quantitative techniques and cartographically represented through maps and diagrams. The main findings is that most of the Oraon tribal peoples are suffering from malnutrition due to the lack of necessary food availability, intake monotonous diets and they are mainly depend on agricultural activities which are not provides the sufficient food stuffs because low agricultural production is found in the study area due to the use of traditional agrarian method, lack of irrigational facility, not used the modern agricultural technology and poor economic conditions etc. The variation of emerging nutritional levels is remarkable concentrated among the Oraon tribes in different parts of the study area.